Day of the Dragon King - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1998)
The magic treehouse takes Jack and Annie back two thousand years to ancient China where they must find the original copy of an old legend before the Imperial Library is burned down by the evil Dragon King.
"A Stepping Stone book."
380
380
Accelerated Reader AR
Keywords: Historical fiction; Time travel -- Fiction; Magic -- Fiction; Tree houses -- Fiction; China -- History -- Han dynasty, 202 B.C.-220 A.D. -- Fiction